2002
DOI: 10.1192/bjp.181.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Fatal and non-fatal repetition of self-harm

Abstract: After 1 year, non-fatal repetition rates are around 15%. The strong connection between self-harm and later suicide lies somewhere between 0.5% and 2% after 1 year and above 5% after 9 years. Suicide risk among self-harm patients is hundreds of times higher than in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
787
13
36

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,101 publications
(874 citation statements)
references
References 88 publications
38
787
13
36
Order By: Relevance
“…For instance, the SADPERSONS tool, a risk assessment based on recognised demographic and clinical factors, does not predict individuals requiring psychiatric admission or community aftercare, or those who repeat self-harm (Quinlivan et al, 2016;Saunders et al, 2014). Currently, the most important predictor of future self-harm and suicide is past self-harm Owens et al, 2002). However, most people who self-harmed will not reattempt and will not die by suicide (Owens et al, 2002).…”
Section: What Do We Currently Understand Predicts Self-harm and Repetmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the SADPERSONS tool, a risk assessment based on recognised demographic and clinical factors, does not predict individuals requiring psychiatric admission or community aftercare, or those who repeat self-harm (Quinlivan et al, 2016;Saunders et al, 2014). Currently, the most important predictor of future self-harm and suicide is past self-harm Owens et al, 2002). However, most people who self-harmed will not reattempt and will not die by suicide (Owens et al, 2002).…”
Section: What Do We Currently Understand Predicts Self-harm and Repetmentioning
confidence: 99%
“…Currently, the most important predictor of future self-harm and suicide is past self-harm Owens et al, 2002). However, most people who self-harmed will not reattempt and will not die by suicide (Owens et al, 2002). Therefore, the predictive value of clinical and demographic parameters alone is weak, and in light of the increasing incidence of suicide, assessment using additional factors is required to accurately predict future self-harm.…”
Section: What Do We Currently Understand Predicts Self-harm and Repetmentioning
confidence: 99%
See 1 more Smart Citation
“…Although around 60 times greater than the population rate, in the UK the incidence is probably somewhere in the region of one in a hundred patients within the first year (Owens et al, 2002;Carroll et al, 2014). But the risk is far higher in certain subgroups and goes on rising over many years after an index episode of non-fatal self-harm.…”
Section: Resultsmentioning
confidence: 97%
“…3 Although suicidal intent is considered low for children and adolescents 4 and the long-term risk of death by suicide after a self-harm event is similarly low (approximately 1% at 10 years), 4,5 visits to the emergency department (ED) for self-harm may be more strongly associated with the intent to die. [5][6][7] A recently published Canadian study found that only 1 in 3 adolescents in Ontario who presented to the ED for self-harm were admitted to hospital. 8 While discharge can be considered for children and adolescents who are not actively suicidal, do not have access to lethal means, and have a responsible adult to ensure their safety, post-ED visit mental health care follow-up should be in place.…”
Section: Introductionmentioning
confidence: 99%